PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN GIANYAR - Rismayanthi, Ni Wayan; Supriliyani, Ni Wayan; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2024)
The purpose of this study is to determine how officials at the Gianyar District Regional Development Planning Agency function in relation to a democratic leadership style. This study employs correlation-based quantitative methodologies.Saturated sampling techniques were used to distribute questionnaires to every BAPPEDA officer in the Gianyar area in order to gather primary data. The degree of difference between the official performance factors and the democratic leadership style variables is determined in this study using a basic linear regression analysis test. The study's findings indicate that a democratic leadership style positively affects official performance, with an R2 of 0.916, meaning that 83.9% of officials perform better when they have a democratic leadership style. According to the significance test results, which were 16.269 greater than the table (2,008) with a significance level of 0.000, staff performance is positively and significantly impacted by democratic leadership. Effective leadership is a reflection of the staff's good work. To maximize the achievement of the organization's objectives, the Gianyar district's Regional Development Planning Agency must uphold and use a democratic leadership style in order to boost employee performance. Keywords: Democratic Leadership Style, Employee Performance, Gianyar Regency Regional Development Planning Agency